Merencanakan Sumber Belajar Berbasis Keterampilan Berperspektif Islami untuk Pendidikan Keanekaragaman Hayati - Eni Setyowati (Ta'allum: Jurnal Pendidikan Islam, 2014)
Educators are beginning to recognize the importance and benefits of introducing pupils to biodiversity and associated issues. Generic criteria for successfully planning and developing a skills-based resource for Islamic perspective biodiversity education are described. The criteria presented here are general to be applied to any biodiversity education and they form a useful framework to construct a resource. Without such a framework there is danger that the biodiversity concept could be misrepresented.